SMK BERBASIS TEKNOLOGI DI ERA OTONOMI DAERAH (PERMASALAHAN DAN TANTANGAN) - Voenli, Voenli (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
The establishment of Vocational Schools (SMK) must meet the availability of practical facilities and infrastructure in accordance with their vocational, implementation of educational autonomy is faced with an existing problem in the regions, namely the ability of the regions to carry out education, especially in relation to the provision of necessary funds. Vocational High School 1 Benakat is the first State Vocational School established by Muara Enim Regency Government after education autonomy. this study researchers used data collection with observation, analysis, and documentation of activities carried out during the learning process and Computer Based National Examination Activities and National Standardized School Test Activities Based on Android and Computers Class XII of SMK Negeri 1 Benakat Academic Year 2018/2019. In order to realize technology-based SMK both in learning and repetition activities and examinations of State Vocational High School 1 benakat independently, the Principal with the agreement of the school community to optimize the utilization and use of BOS funds.